Does digital literacy affect farmers' adoption of agricultural social services? An empirical study based on China Land Economic Survey data. - Yanfei Wang; Guandong Xu; Jie Cao; Yanchi Chen; Jia Wu (PLoS ONE)
Agricultural social services (ASS) are crucial in alleviating resource constraints and advancing agricultural modernization. Using the data derived from the China Land Economic Survey (CLES2022), this study empirically investigates how digital literacy influences farmers' adoption of ASS, employing both Probit and Propensity score matching (PSM) models. Additionally, it explores the mediating roles of long-term production vision and part-time employment degrees in this relationship. The findings are: (1) digital literacy exhibited a statistically significant positive effect on farmers' adoption of ASS at the 1% significant level. Moreover, this impact varied among participants in technology training, different education levels, and varying levels of risk preference; (2) long-term production vision and part-time employment degrees act as mediators, enhancing the positive impact of digital literacy on farmers' adoption of ASS. Based on these findings, recommendations have been developed to improve farmers' digital literacy, promote the adoption of ASS, and enhance farmers' long-term production vision as well as degree of part-time.